Creep analysis of steel-concrete composite beams using generalized beam theory - Henriques, David (2018)
This paper presents the latest developments concerning the numerical modelling of steelconcrete composite beams using finite elements based on Generalized Beam Theory (GBT). In particular, this paper is dedicated to showing that GBT makes it possible to obtain, with significant accuracy and computational efficiency, the combined effects of creep and shear lag. In order to capture these effects, shear lag deformation modes are added to the beam kinematic description and the influence of creep is taken into account through a linear viscoelastic law which is written as a Dirichlet series expansion. An illustrative numerical example is presented, to show the capabilities and potential of the proposed GBT-based finite element formulation.